2015
DOI: 10.1038/ncomms7323
|View full text |Cite|
|
Sign up to set email alerts
|

The NCA sodium leak channel is required for persistent motor circuit activity that sustains locomotion

Abstract: Persistent neural activity, a sustained circuit output that outlasts the stimuli, underlies shortterm or working memory, as well as various mental representations. Molecular mechanisms that underlie persistent activity are not well understood. Combining in situ whole-cell patch clamping and quantitative locomotion analyses, we show here that the Caenorhabditis elegans neuromuscular system exhibits persistent rhythmic activity, and such an activity contributes to the sustainability of basal locomotion, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
100
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(116 citation statements)
references
References 57 publications
16
100
0
Order By: Relevance
“…Similarly, dop-3 expression in the command interneurons was sufficient to reverse the dop-3 suppression of the slow locomotion of grk-2 mutants (Fig 8G). Given that the fainting phenotypes of nlf-1 mutants and nca mutants were also rescued by expression in command interneurons [43,91], our results suggest that GRK-2, DOP-3, and the NCA channels act in the same neurons. However, we did not see rescue of the grk-2 locomotion phenotype using the glr-1 promoter (Fig 3A), which in principle is also expressed in the command interneurons, and similarly we did not observe statistically significant rescue of the nlf-1 fainting phenotype using the same glr-1 promoter [12].…”
Section: Grk-2 and Dop-3 Act In Command Interneurons To Control Grk-2mentioning
confidence: 82%
See 2 more Smart Citations
“…Similarly, dop-3 expression in the command interneurons was sufficient to reverse the dop-3 suppression of the slow locomotion of grk-2 mutants (Fig 8G). Given that the fainting phenotypes of nlf-1 mutants and nca mutants were also rescued by expression in command interneurons [43,91], our results suggest that GRK-2, DOP-3, and the NCA channels act in the same neurons. However, we did not see rescue of the grk-2 locomotion phenotype using the glr-1 promoter (Fig 3A), which in principle is also expressed in the command interneurons, and similarly we did not observe statistically significant rescue of the nlf-1 fainting phenotype using the same glr-1 promoter [12].…”
Section: Grk-2 and Dop-3 Act In Command Interneurons To Control Grk-2mentioning
confidence: 82%
“…In C. elegans, the NCA channels act in premotor interneurons [12,43,91]. To determine whether grk-2 acts in a cell autonomous way to regulate NCA, we identified the head acetylcholine neurons where GRK-2 is expressed.…”
Section: Grk-2 and Dop-3 Act In Command Interneurons To Control Grk-2mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that NALCN contributes to sustained depolarization and spike trains in interstitial cells of Cajal and hermaphroditespecific neurons in C. elegans [28,37]. Our laboratory also demonstrated that NALCN contributes to the leak current in human myometrium [29].…”
Section: Nalcn Expression In the Mouse Uterusmentioning
confidence: 53%
“…Because NALCN lacks several charged residues in the putative voltage-sensing domain, this channel is voltage-insensitive and constitutively active [25]. The Na + leak activity of NALCN is essential for depolarizing the membrane potential, promoting spontaneous firing, and sustaining rhythmic burst activity in other spontaneously active cells [25][26][27][28]. We reported that NALCN is expressed in human myometrial myocytes and contributes to the leak current in myocytes from pregnant women [29].…”
Section: +mentioning
confidence: 99%